Gendered Labor Rights Under Taliban Rule: Addressing Employment Inequality in Post-2021 Afghanistan - Haidari, Adila (International Journal Administration, Business & Organization, 2024)
The Taliban's takeover of Afghanistan on August 15, 2021, marked a pivotal moment in the nation's history and had profound implications for women's labor rights. This policy brief identifies the drastic reduction in women employment as a profound socioeconomic challenge, exacerbated by the de facto authority’s restrictive policies towards women in the workforce. The study uniquely focuses on the intersection of gender and labor rights after regime change, analyzing the growing barriers to women's employment, which not only undermines gender equality but also threatens the broader socioeconomic stability of Afghanistan. This study aims to propose practical policy recommendations that address these inequalities and advocate for international intervention to protect women's labor rights in Afghanistan. Author utilized qualitative analysis, drawing from diverse policy documents and reports, to understand Afghan women's lived experiences under the Taliban regime. Key findings reveal that the Taliban's governance post-2021 has led to significant setbacks in women's employment across various sectors, contributing to economic regression and deepening gender disparities. The brief urges for international financial support to women-led organizations and the promotion of online and home-based employment, alongside relocation programs and rigorous data monitoring for effective policymaking.